A case of noncardiogenic pulmonary edema and pleural effusion following diclofenac administration - Vinod Kumar; Vasantha Kamath; Shreyashi Ganguly (Wolters Kluwer Medknow Publications, 2021)
The acute manifestations of diclofenac allergy vary from mild urticaria or skin rash to severe and life-threatening complications such as ARDS, and anaphylactic shock. Very few cases of diclofenac allergy have been reported in literature especially with respect to pulmonary manifestations. We are reporting a case of a 31-year-old who presented in respiratory distress consequent to diclofenac hypersensitivity. Our patient had non-cardiogenic pulmonary oedema and bilateral minimal pleural effusion 3 days following diclofenac administration. On examination the patient was conscious, alert and oriented, PR- 88 bpm, BP- 150/100 mmHg, RR-22 cpm temperature 98.6°F with oxygen saturation of 95% on room air. Her respiratory system examination revealed a dull note on percussion and decreased vocal fremitus, decreased vocal resonance, diminished air entry in bilateral infra scapular and infra axillary areas with fine inspiratory crepitations. The diagnosis of ARDS was ruled out as the ratio of PaO2 to FiO2 was 410. After treatment with I.V diuretics, antibiotics and inhalational bronchodilators she improved over a period of 5 days. She had complete resolution of her chest symptoms and chest findings both clinically and radiologically. Pulmonary manifestations such as ARDS, eosinophilic pneumonitis, pleural effusion, eosinophilic pneumonia, pulmonary oedema, hemoptysis, pulmonary infiltrates with eosinophilia and asthmatic attacks are rare. The temporal relationship between symptom onset and drug administration is the most important piece of history while making the diagnosis. History of allergic reaction to NSAIDs should be evaluated in detail. It is therefore important that the physician keep this in mind while prescribing.